Spiritual Motivation in the Quran: Insights from ESQ 165 by Ary Ginanjar Agustian - Abdurrohim, Abdurrohim; Rohmana, Jajang A.; Zulaiha, Eni (Hanifiya: Jurnal Studi Agama-Agama, 2025)
Religion and spirituality are intertwined, with spirituality at the core of religious experience. Recent studies highlight the connection between spirituality and mental health, self-efficacy, and self-respect. In 2001, Ary Ginanjar Agustian introduced ESQ 165, a religious phenomenon aimed at enhancing human resources through spirituality. However, this concept faced criticism from some Islamic scholars, including Malaysian mufti Datuk Hj. Wan Zahidi bin Wan Teh, who argued it contradicts Islamic teachings. Conversely, research by Daromir Rudnyckij links ESQ 165 to "Spiritual Economy," merging Islamic principles with neoliberal economic practices to boost productivity. This qualitative study employs library research to analyze Agustian's interpretations of the Quran in his work "Secrets of Success in Building Spiritual Emotional Intelligence ESQ 165." Findings reveal that ESQ 165 integrates intellectual (IQ), emotional (EQ), and spiritual intelligence (SQ) with Islamic values of Faith, Islam, and Ihsan. Agustian's interpretations differ from traditional ulama due to methodological influences and a psychological approach, positioning them outside conventional interpretation rules. Despite critiques, his insights resonate with Gadamer's understanding of interpretation shaped by personal horizons, aligning ESQ 165 with Quranic spiritual motivation and Danah Zohar's God Spot theory.